Usability Evaluation of Ticket Purchasing Applications, Case Study Public Railways in Indonesia - Lisana, Lisana; Bena, Dea Almira; Sutanto, Jessica Levina; Novandyanta, Evan; Kevin, Kevin (ULTIMA InfoSys, 2024)
This study aims to evaluate the usability of a mobile-based application used to facilitate passengers in purchasing train tickets, the Access by KAI application. As an application widely used by the public, the usability evaluation is essential. The evaluation was conducted by measuring usability in three aspects: effectiveness, efficiency, and user satisfaction. The measurement involved 10 respondents who actively use the application. They performed the experiment at the usability laboratory. The level of effectiveness and efficiency was measured using task analysis, analyzing the final results of each respondent after performing five predetermined tasks. The results show that the effectiveness and efficiency of the application are good. However, the measurement of user satisfaction aspect using the SUS (System Usability Scale) method indicates less favorable results. This obviously results in poor user experience (UX) for users. Therefore, the practical implication of this study is the need for improvements to the application, both in the user interface (UI) and existing business processes, to enhance the user experience.